EXTH-30. IN SITU AUTOVACCINATION MEDIATED BY ONCOLYTIC ADENOVIRUS DELTA-24-RGDOX INDUCES EFFICACIOUS IMMUNITY AGAINST METASTATIC MELANOMA. (5th November 2018) - Jiang, Hong; Nguyen, Teresa; Ho Shi, Dong; Fan, Xuejun; Gumin, Joy; Bernatchez, Chantale; Lang, Frederick; Gomez-Manzano, Candelaria; Fueyo, Juan
Abstract: We have reported that Delta-24-RGDOX, an oncolytic adenovirus expressing the immune co-stimulator OX40 ligand (OX40L), induces efficacious anti-glioma immunity in syngeneic intracranial glioma models of immune competent mice. Here we sought to determine if the local injection of the virus triggers a systemic immune response against metastatic melanomas. We found that Delta-24-RGDOX expressed OX40L and induced cell lysis in both human and mouse melanoma cells. To study the abscopal effect of Delta-24-RGDOX against metastatic melanomas, we established s.c./s.c. and s.c./i.c. melanoma models with B16-Red-FLuc cells in C57BL/6 mice. In the s.c./s.c. model, we found that three doses of intratumoral injection of the virus significantly inhibited the growth of the injected and the untreated distant tumors, resulting in prolonged survival of the mice (70% long-term survival; P = 0.001). The surviving mice were resistant to a rechallenging with the implantation of similar tumor cells, but not when lung cancer cells were implanted, strongly suggesting the development of specific tumor immune memory. Using flow cytometry analysis, we found that Delta-24-RGDOX treatment resulted in increased frequency of CD3+ T lymphocytes, CD3+CD4+ helper T cells, CD3+CD8+ cytotoxic T cells and effector T cells, and a decrease in the amount of T regulatory cells. In addition, we observed an increment of effector CD4+ and CD8+ T cells frequency with PD-1 expression on spleen and blood cells, indicating a systemic activation of anti-tumor circulatory cells. In the s.c./i.c. model, viral injection into the s.c. tumor induced anti-melanoma activity in the brain, resulting in growth inhibition of both tumors and prolonged survival of the animals. In agreement with these data, viral injection in the s.c. tumor increased the frequency of the T effector cells in the brain tumor. In summary, local treatment of melanoma with Delta-24-RGDOX results in suppression of distant tumors including brain melanoma.